The ANALYSIS OF GROSS PROFIT OF TRANSPORTATION AND LOGISTICS COMPANIES (Case Study at Samudera Indonesia Company, Tbk) - Nurul Wahidatun Nisa' (Al-Idarah, 2023)
This study aims to determine the condition of the company's gross profit and the influencing factors in the 2020-2022 period. This study uses a descriptive method involving gross profit variables. The data that being used in this research comes from the company's income statement which is published on the official website of the Indonesia Stock Exchange. The results of this research showed that PT Samudera Indonesia, Tbk's gross profit experienced a continuous increase from 2020 to 2022. Gross profit in 2021 increased by 186.67% compared to 2020, and gross profit in 2022 increased by 107.6% compared to 2021. Several factors contributed to the high and low of the PT Samudera Indonesia, Tbk gross profit, namely: cost, selling prices, service sales volume, and global economic conditions.